Membrane Cholesterol Is a Critical Determinant for Hippocampal Neuronal Polarity - Jose, Mini; Sivanand, Aiswarya; Channakeshava, Chaitra (Frontiers in Molecular Neuroscience, 2021)
Maintaining the normal cholesterol balance is crucial for the functioning of a healthy brain. Dysregulation in cholesterol metabolism and homeostasis in the brain have been correlated to various neurological disorders. The majority of previous studies in primary cultures focus on the role of cholesterol balance in neuronal development after polarity has been established. Here we have investigated how transient alteration of membrane lipids, specifically cholesterol, affects neuronal development and polarity in developing hippocampal neurons prior to polarity establishment, soon after initiation of neurite outgrowth. We observed that temporary cholesterol perturbation affects axonal and dendritic development differentially in an opposing manner. Transient membrane cholesterol deficiency increased neuronal population with a single neurite, simultaneously generating a second population of neurons with supernumerary axons. Brief replenishment of cholesterol immediately after cholesterol sequestering rescued neuronal development defects and restored polarity. The results showed a small window of cholesterol concentration to be complementing neurite outgrowth, polarity reestablishment and in determining the normal neuronal morphology, emphasizing the critical role of precise membrane lipid balance in defining the neuronal architecture. Membrane cholesterol enhancement altered neurite outgrowth but did not significantly alter polarity. Cholesterol sequestering at later stages of development have shown to enhance neurite outgrowth, whereas distinct effects for neurite development and polarity were observed at early developmental stages, signifying the relevance of precise membrane cholesterol balance in altering the neuronal physiology. Our results confirm cholesterol to be a key determinant for axo-dendritic specification and neuronal architecture and emphasize the possibility to reverse neuronal developmental defects caused by cholesterol deficiency by modulating membrane cholesterol during the early developmental stages.